Design of Inventory Management Information System (Si Menris) Kamoning Community Health Center Website Based - Safiuddin, Safiuddin; Fahmi, Zainol; Putra, Fauzan Prasetyo Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
At the Puskesmas Kamoning health facility, inventory management is still done manually using paper, Microsoft Excel, and Google Spreadsheets shared via WhatsApp. So it's difficult for officers to organise the data and monitor the stock of goods with the available data. It's becoming inefficient and less accurate. In addition, there are limited working hours for accessing equipment data until data is lost or duplication occurs. The researchers developed a web-based inventory information system to replace the manual process. The system will make inventory management easier, ranging from recording to monitoring to stock management, and will also meet information needs faster and more accurately. Stages and procedures for designing an inventory management information system (Si Menris) using the waterfall model. PHP and CSS are programming languages supported by MySQL as a data storage database. This system uses black box testing to test errors in the system. This Inventory Management Information System (Si Menris) helps inventory management get more accurate, faster data. Besides that, the system can make it easier for employees to make inventory service complaints.